ChemInform Abstract: Direct Synthesis of Cyclic Imides from Carboxylic Anhydrides and Amines by Nb2O5 as a Water‐Tolerant Lewis Acid Catalyst. Issue 28 (June 2016) - Ali, Md. A.; Moromi, Sondomoyee K.; Touchy, Abeda S.; Shimizu, Ken‐ichi
Abstract: The target compounds, important synthons for chemical and biological applications, are readily available from different carboxylic anhydrides and primary amines or gaseous ammonia.